2020
DOI: 10.1017/s1755773920000144
|View full text |Cite
|
Sign up to set email alerts
|

Jobs at risk? Task routineness, offshorability, and attitudes toward immigration

Abstract: In this paper, we study the relationship between occupational vulnerability and attitudes toward immigration in Western Europe. We measure occupational vulnerability as the risk of unemployment due to routine-biased technological change and offshoring of jobs to other countries. Previous empirical studies in political economy have shown that individuals' policy preferences echo their economic risks and prospects. Workers in low routine occupations are most worried about their job market prospects, most likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 68 publications
(113 reference statements)
1
16
0
Order By: Relevance
“…First, the findings provide evidence in line with studies suggesting a non‐negligible economic basis of immigration policy attitudes focusing on prospective status in labour markets (Dancygier & Walter, 2015; Kaihovaara & Im, 2020; Pardos‐Prado & Xena, 2019; Pecoraro & Ruedin, 2016). Contributing to such debates, I suggested that less immigration may be desirable for the relatively more risk exposed as it provides an ex ante damper on stopping further uncertainty.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…First, the findings provide evidence in line with studies suggesting a non‐negligible economic basis of immigration policy attitudes focusing on prospective status in labour markets (Dancygier & Walter, 2015; Kaihovaara & Im, 2020; Pardos‐Prado & Xena, 2019; Pecoraro & Ruedin, 2016). Contributing to such debates, I suggested that less immigration may be desirable for the relatively more risk exposed as it provides an ex ante damper on stopping further uncertainty.…”
Section: Discussionsupporting
confidence: 85%
“…The average number of individual‐level observations in each country‐year unit is 740. Given my theoretical focus on the risk of being unemployed instead of the unemployment status, the analysis is restricted to actively employed respondents similar to comparable work (Kaihovaara & Im, 2020; Polavieja, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations